Technical and environmental efficiency of hog production in China – A stochastic frontier production function analysis - Ying-heng ZHOU; Xiao-heng ZHANG; Xu TIAN; Xian-hui GENG; Peng ZHANG; Bin-jian YAN (Journal of Integrative Agriculture, 2015)
This article analyses the technical and environmental efficiency of hog production in China using data from the China Agricultural Product Cost-Benefit Compilation (NDRC 2005–2013) and the First National Census of Pollution: Manual of Discharge Coefficient of Livestock and Poultry Industry (IEDA and NIES 2009). The empirical results show a great variation in environmental efficiency, ranging from 0.344 to 0.973 with a mean value of 0.672 that declines over time. Southwest China is found to be the most environmentally efficient region, while the Northeast and the Northwest are the least efficient. Another finding is that technical and environmental efficiencies are highly correlated in hog production; the most environmentally efficient regions are usually found to have high technical efficiency, and vice versa. In addition, we computed the output elasticities with respect to each factor input. The results show that feed is the most efficient input, with an output elasticity of approximately 0.551, which is much higher than the elasticity of the nitrogen surplus, other capital or labour. The output elasticity with respect to the nitrogen surplus is 0.287 on average. Finally, the scale elasticity in hog production is slightly higher than 1.